A Low Dynamic Deviation and High Robustness Position Control Strategy Based on Virtual Reference - Tao Liu; Qiaoling Tong; Qiao Zhang; Kan Liu (IEEE Access, 2022)
This paper proposes a modified model predictive control method with the virtual model (VM-MPC) to generate a virtual reference of the position loop. The dynamic deviation is introduced into the virtual reference as a position advance. Applying this virtual reference as the input of position controllers, the dynamic response is greatly improved without changing the gain of position controllers. Therefore, both the dynamic response and robustness of the position loop are improved when the response delay of the speed loop is uncertain. In order to reduce the influence of model mismatch on model predictive control, instead of the actual feedback, a virtual model feedback of the expected position response is used. With this approach, control parameters of VM-MPC are optimized offline to obtain the fast position response without overshoot. A model compensator is proposed to reduce the mismatch between the virtual model and the real system. The effectiveness and feasibility of the proposed method are verified by simulation and experiment results.